2013
DOI: 10.1165/rcmb.2011-0320oc
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil Factor–2 Reverses Airway Remodeling Changes in Allergic Airways Disease

Abstract: Trefoil factor 2 (TFF2) is a small peptide with an important role in mucosal repair. TFF2 is up-regulated in asthma, suggesting a role in asthma pathogenesis. Given its known biological role in promoting epithelial repair, TFF2 might be expected to exert a protective function in limiting the progression of airway remodeling in asthma. The contribution of TFF2 to airway remodeling in asthma was investigated by examining the expression of TFF2 in the airway and lung, and evaluating the effects of recombinant TFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…Annexin V-associated apoptosis was also significantly higher in OVA-sensitized/ challenged mice compared to that measured in saline controls, 25 and was further increased in OVA þ NA-treated mice compared with OVA-sensitized/challenged animals, which was comparable to levels measured in NA alonetreated mice. As epithelial denudation was not observed in Figure 5 Determination of airway resistance from dose-response to methacholine.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Annexin V-associated apoptosis was also significantly higher in OVA-sensitized/ challenged mice compared to that measured in saline controls, 25 and was further increased in OVA þ NA-treated mice compared with OVA-sensitized/challenged animals, which was comparable to levels measured in NA alonetreated mice. As epithelial denudation was not observed in Figure 5 Determination of airway resistance from dose-response to methacholine.…”
Section: Discussionsupporting
confidence: 53%
“…Characterization of a novel model of asthma SG Royce et al repair peptide, trefoil factor 2, 23,25 it can be suggested that epithelial damage alone can lead to subepithelial airway fibrosis (as demonstrated by the increased NA-induced subepithelial collagen thickness and total lung collagen concentration), similar to processes occurring in human asthma where repeated episodes of epithelial injury lead to prolonged activation of the epithelial mesenchymal trophic unit. 26,27 Previous studies have shown that epithelial damage results in epithelial cells releasing pro-inflammatory factors such as IL-1 and tumor necrosis factor-a.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Various reports have demonstrated the reversal of airway remodeling with a 14-day treatment protocol [13,14]. The major difference between our approach in this study and these published approaches was the continuation of the OVA challenge; in the previous reports, the challenge was stopped during treatment.…”
Section: Methodsmentioning
confidence: 95%